Peran Promosi dan Proses dalam Mempengaruhi Keputusan Gunakan Dompet Digital LinkAja - Yudha Mahrom DS; Nadia Afrilliana; Fagar Fertiwi Fardah Tunisa Ahmad; Anisa Permata Sari (Universitas Muhammadiyah Palembang, 2025)
Purpose – This study aims to examine the influence of promotion and process on the decision to use the LinkAja digital wallet application in Seberang Ulu II District, Palembang City Design/methodology – This study employs an associative quantitative approach with data collected through questionnaires and documentation. The population consists of LinkAja application users in Seberang Ulu II District, which is considered an infinite population. A total of 97 respondents were selected using purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS. Findings - The results of the study show that promotion and process simultaneously have a significant influence on the decision to use the LinkAja application. Partially, both promotion and process individually also have a positive and significant effect on usage decisions. This study provides implications for companies to optimize promotional strategies and simplify service processes to enhance customer satisfaction and usage decisions